1998
DOI: 10.1017/s0048577298961492
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static forehead and forearm muscle tension on total respiratory resistance in healthy and asthmatic participants

Abstract: The impact of static muscle tension on total respiratory resistance (TRR) was examined. Participants (24 healthy, 24 asthmatic) performed biofeedback-assisted sequences of tensing (15 s) and relaxing (20 s) forehead and forearm muscles. Muscle tension levels were 40% or 80% of the maximum individual force. Oscillatory TRR, electromyograms, ventilation, heart period, and respiratory sinus arrhythmia were recorded. Baseline TRR did not change over the session as a whole. Decreases in TRR during forehead tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…We have observed substantial increases in FRC during a biofeedbackassisted facial muscle tension task in healthy and asthmatic individuals (Ritz, Dahme, & Wagner, 1998). Similarly, increases in FRC have been observed during posing of emotional facial expressions, which was related to ratings of effort and heart rate accelerations (Boiten, 1996).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…We have observed substantial increases in FRC during a biofeedbackassisted facial muscle tension task in healthy and asthmatic individuals (Ritz, Dahme, & Wagner, 1998). Similarly, increases in FRC have been observed during posing of emotional facial expressions, which was related to ratings of effort and heart rate accelerations (Boiten, 1996).…”
Section: Introductionsupporting
confidence: 58%
“…Finally, future studies should also determine the specificity of the respiratory muscle -dyspnea association in comparison with other skeletal muscles sites such as forehead or leg muscles. This will also have to take into account bronchodilatory effects of skeletal muscle tension (Freedman, 1992;Ritz et al, 1998;Rybicki et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…On average, initial lung function was close to 100% of predicted, and bronchodilator medication use The range of applicability of hypoventilation training for asthma patients remains to be determined. Although excessive minute ventilation and low pCO 2 are often reported in asthma (Osborne, O'Connor, Lewis, et al 2000;Ritz, Dahme, & Wagner, 1998;Varray & Prefaut, 1992, Kelsen, Fleegler, & Altose, 1979, a sizable number of patients show normal or close to normal levels of pCO 2 . The target for such patients can be stabilization of normal levels of pCO 2 by more regular breathing.…”
Section: Discussionmentioning
confidence: 99%
“…While oxygen saturation is usaully normal in asthma patients except for periods of severe exacerbation (Wagner, Hedenstierna, & Rodriguez-Roisin, 1996)), studies have found lower resting pCO 2 in patients than in healthy controls (Hombrey et al, 1988;Osborne, O'Connor, Lewis, et al 2000;Ritz, Wilhelm, Meuret, & Roth, 2003) or stronger minute ventilation or respiratory drive at baseline or in response to exercise (Ritz, Dahme, Wagner, 1998;Varray, Prefaut, 1992), added resistive loads (Kelsen, Fleegler, & Altose, 1979), or methacholine-induced bronchoconstriction (Fujimori et al, 1996).…”
mentioning
confidence: 99%
“…Physical activity can be an important source of variance in assessments of lung function. Dynamic and static muscle activation can dilate the airways of healthy and asthmatic individuals [e.g., [28,29]]. In asthmatic patients, longer or more intense periods of physical exercise can lead to exercise-induced asthma, in which the airways often constrict with a peak response 10-20 min following the activity [30].…”
Section: Diary Ratingsmentioning
confidence: 99%